On the Poincaré theorem with asymptotically periodic coefficients - Buslaeva, S. F. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We consider the case where the Poincaré theorem for difference equations with asymptotically constant coefficients is generalized to systems of difference equations with asymptotically periodic coefficients.